Upaya Membangun Citra Lembaga Melalui Strategi Kepala Sekolah di SMK Ma’arif 6 Ayah Kebumen - Nadhirotul Munawaroh; Imam Subarkah; Devi Yaniar Wi Hargina (IAINU Kebumen, 2023)
This study aims to describe effort building the image of institution through the principal’s strategy at SMK Ma’arif 6 Ayah Kebumen. The method used in this study is a qualitative research method. Data collection techniques used is using observation, interviews and documentation. The main informants in this study were principal, and the supporting informants were the vice head of student affairs, the deputy head of industrial relations and the head of special job market. Based on the results of the study, it can be concluded that the principal’s strategy in building the image of the institution at SMK Ma’arif 6 Ayah Kebumen is, (1) By marketing the special job market, (2) through student achievement, (3) By accommodation in the community, (4) Through public service, and (5) By increasing the human resources of educators.